![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
Expand each of the following, using suitable identities:
$(i) {\left( {x + 2y + 4z} \right)^2}$ $(ii) {\left( {2x - y + z} \right)^2}$ $(iii) {\left( { - 2x + 3y + 2z} \right)^2}$ $(iv) {\left( {3a - 7b - c} \right)^2}$ $(v) {\left( { - 2x + 5y - 3z} \right)^2}$ $(iv) {\left( {\dfrac{1}{4}a - \dfrac{1}{2}b + 1} \right)^2}$
Answer
513k+ views
Hint: Let’s substitute the values of a, b and c in the formula given below for determining the square of sum of three numbers and reach the answer by simplifying.
$ \Rightarrow {\left( {a + b + c} \right)^2} = {a^2} + {b^2} + {c^2} + 2\left( {ab + bc + ac} \right)$
Complete step-by-step answer:
All the above parts of the question contain the form of ${\left( {a + b + c} \right)^2}$ , and as we know that:
${\left( {a + b + c} \right)^2} = {a^2} + {b^2} + {c^2} + 2\left( {ab + bc + ac} \right),$ we will use this formula for expanding every expression:
$(i)$ If we compare ${\left( {x + 2y + 4z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = x,b = 2y$ and $c = 4z$. Thus, using the formula, we’ll get:
$
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = {x^2} + {\left( {2y} \right)^2} + {\left( {4z} \right)^2} + 2\left( {x.2y + 2y.4z + x.4z} \right), \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = {x^2} + 4{y^2} + 16{z^2} + 4xy + 16yz + 8xz \\
$
$(ii)$ If we compare ${\left( {2x - y + z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = 2x,b = - y$ and $c = z$. Thus, using the formula, we’ll get:
$
\Rightarrow {\left( {2x - y + z} \right)^2} = {\left( {2x} \right)^2} + {\left( { - y} \right)^2} + {z^2} + 2\left[ {2x.\left( { - y} \right) + \left( { - y} \right).z + 2x.z} \right], \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = 4{x^2} + {y^2} + {z^2} - 4xy - 2yz + 4xz \\
$
$(iii)$ If we compare ${\left( { - 2x + 3y + 2z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = - 2x,b = 3y$ and $c = 2z$. Thus, using the formula, we’ll get:
$
\Rightarrow {\left( { - 2x + 3y + 2z} \right)^2} = {\left( { - 2x} \right)^2} + {\left( {3y} \right)^2} + {\left( {2z} \right)^2} + 2\left[ {\left( { - 2x} \right).3y + 3y.2z + \left( { - 2x} \right).2z} \right], \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = 4{x^2} + 9{y^2} + 4{z^2} - 12xy + 12yz - 8xz \\
$
$(iv)$ If we compare ${\left( {3a - 7b - c} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, in place of a, b and c here we have 3a, -7b and –c respectively. Thus, using the formula, we’ll get:
\[ \Rightarrow {\left( {3a - 7b - c} \right)^2} = {\left( {3a} \right)^2} + {\left( { - 7b} \right)^2} + {\left( { - c} \right)^2} + 2\left[ {3a.\left( { - 7b} \right) + \left( { - 7b} \right).\left( { - c} \right) + 3a.\left( { - c} \right)} \right],\]
\[ \Rightarrow {\left( {3a - 7b - c} \right)^2} = 9{a^2} + 49{b^2} + {c^2} - 42ab + 14bc - 6ac\]
$(v)$ If we compare ${\left( { - 2x + 5y - 3z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = - 2x,b = 5y$ and $c = - 3z$. Thus, using the formula, we’ll get:
\[
\Rightarrow {\left( { - 2x + 5y - 3z} \right)^2} = {\left( { - 2x} \right)^2} + {\left( {5y} \right)^2} + {\left( { - 3z} \right)^2} + 2\left[ {\left( { - 2x} \right).5y + 5y.\left( { - 3z} \right) + \left( { - 2x} \right).\left( { - 3z} \right)} \right], \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = 4{x^2} + 25{y^2} + 9{z^2} - 20xy - 30yz + 12xz \\
\]
$(vi)$ If we compare ${\left( {\dfrac{1}{4}a - \dfrac{1}{2}b + 1} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, in place of a, b and c here we have $\dfrac{1}{4}a, - \dfrac{1}{2}b$ and 1 respectively. Thus, using the formula, we’ll get:
\[
\Rightarrow {\left( {\dfrac{1}{4}a - \dfrac{1}{2}b + 1} \right)^2} = {\left( {\dfrac{1}{4}a} \right)^2} + {\left( { - \dfrac{1}{2}b} \right)^2} + {1^2} + 2\left[ {\left( {\dfrac{1}{4}a} \right).\left( { - \dfrac{1}{2}b} \right) + \left( { - \dfrac{1}{2}b} \right).\left( 1 \right) + \left( {\dfrac{1}{4}a} \right).\left( 1 \right)} \right], \\
\Rightarrow {\left( {\dfrac{1}{4}a - \dfrac{1}{2}b + 1} \right)^2} = \dfrac{1}{{16}}{a^2} + \dfrac{1}{4}{b^2} + 1 - \dfrac{1}{4}ab - b + \dfrac{1}{2}a. \\
\]
Note: If we miss the formula for ${\left( {a + b + c} \right)^2}$, we can apply general multiplication method for expanding the above expressions:
$
\Rightarrow {\left( {a + b + c} \right)^2} = \left( {a + b + c} \right).\left( {a + b + c} \right), \\
\Rightarrow {\left( {a + b + c} \right)^2} = a\left( {a + b + c} \right) + b\left( {a + b + c} \right) + c\left( {a + b + c} \right) \\
$
On expansion, we’ll get the same result.
$ \Rightarrow {\left( {a + b + c} \right)^2} = {a^2} + {b^2} + {c^2} + 2\left( {ab + bc + ac} \right)$
Complete step-by-step answer:
All the above parts of the question contain the form of ${\left( {a + b + c} \right)^2}$ , and as we know that:
${\left( {a + b + c} \right)^2} = {a^2} + {b^2} + {c^2} + 2\left( {ab + bc + ac} \right),$ we will use this formula for expanding every expression:
$(i)$ If we compare ${\left( {x + 2y + 4z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = x,b = 2y$ and $c = 4z$. Thus, using the formula, we’ll get:
$
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = {x^2} + {\left( {2y} \right)^2} + {\left( {4z} \right)^2} + 2\left( {x.2y + 2y.4z + x.4z} \right), \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = {x^2} + 4{y^2} + 16{z^2} + 4xy + 16yz + 8xz \\
$
$(ii)$ If we compare ${\left( {2x - y + z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = 2x,b = - y$ and $c = z$. Thus, using the formula, we’ll get:
$
\Rightarrow {\left( {2x - y + z} \right)^2} = {\left( {2x} \right)^2} + {\left( { - y} \right)^2} + {z^2} + 2\left[ {2x.\left( { - y} \right) + \left( { - y} \right).z + 2x.z} \right], \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = 4{x^2} + {y^2} + {z^2} - 4xy - 2yz + 4xz \\
$
$(iii)$ If we compare ${\left( { - 2x + 3y + 2z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = - 2x,b = 3y$ and $c = 2z$. Thus, using the formula, we’ll get:
$
\Rightarrow {\left( { - 2x + 3y + 2z} \right)^2} = {\left( { - 2x} \right)^2} + {\left( {3y} \right)^2} + {\left( {2z} \right)^2} + 2\left[ {\left( { - 2x} \right).3y + 3y.2z + \left( { - 2x} \right).2z} \right], \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = 4{x^2} + 9{y^2} + 4{z^2} - 12xy + 12yz - 8xz \\
$
$(iv)$ If we compare ${\left( {3a - 7b - c} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, in place of a, b and c here we have 3a, -7b and –c respectively. Thus, using the formula, we’ll get:
\[ \Rightarrow {\left( {3a - 7b - c} \right)^2} = {\left( {3a} \right)^2} + {\left( { - 7b} \right)^2} + {\left( { - c} \right)^2} + 2\left[ {3a.\left( { - 7b} \right) + \left( { - 7b} \right).\left( { - c} \right) + 3a.\left( { - c} \right)} \right],\]
\[ \Rightarrow {\left( {3a - 7b - c} \right)^2} = 9{a^2} + 49{b^2} + {c^2} - 42ab + 14bc - 6ac\]
$(v)$ If we compare ${\left( { - 2x + 5y - 3z} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, we will get $a = - 2x,b = 5y$ and $c = - 3z$. Thus, using the formula, we’ll get:
\[
\Rightarrow {\left( { - 2x + 5y - 3z} \right)^2} = {\left( { - 2x} \right)^2} + {\left( {5y} \right)^2} + {\left( { - 3z} \right)^2} + 2\left[ {\left( { - 2x} \right).5y + 5y.\left( { - 3z} \right) + \left( { - 2x} \right).\left( { - 3z} \right)} \right], \\
\Rightarrow {\left( {x + 2y + 4z} \right)^2} = 4{x^2} + 25{y^2} + 9{z^2} - 20xy - 30yz + 12xz \\
\]
$(vi)$ If we compare ${\left( {\dfrac{1}{4}a - \dfrac{1}{2}b + 1} \right)^2}$ with ${\left( {a + b + c} \right)^2}$, in place of a, b and c here we have $\dfrac{1}{4}a, - \dfrac{1}{2}b$ and 1 respectively. Thus, using the formula, we’ll get:
\[
\Rightarrow {\left( {\dfrac{1}{4}a - \dfrac{1}{2}b + 1} \right)^2} = {\left( {\dfrac{1}{4}a} \right)^2} + {\left( { - \dfrac{1}{2}b} \right)^2} + {1^2} + 2\left[ {\left( {\dfrac{1}{4}a} \right).\left( { - \dfrac{1}{2}b} \right) + \left( { - \dfrac{1}{2}b} \right).\left( 1 \right) + \left( {\dfrac{1}{4}a} \right).\left( 1 \right)} \right], \\
\Rightarrow {\left( {\dfrac{1}{4}a - \dfrac{1}{2}b + 1} \right)^2} = \dfrac{1}{{16}}{a^2} + \dfrac{1}{4}{b^2} + 1 - \dfrac{1}{4}ab - b + \dfrac{1}{2}a. \\
\]
Note: If we miss the formula for ${\left( {a + b + c} \right)^2}$, we can apply general multiplication method for expanding the above expressions:
$
\Rightarrow {\left( {a + b + c} \right)^2} = \left( {a + b + c} \right).\left( {a + b + c} \right), \\
\Rightarrow {\left( {a + b + c} \right)^2} = a\left( {a + b + c} \right) + b\left( {a + b + c} \right) + c\left( {a + b + c} \right) \\
$
On expansion, we’ll get the same result.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The area of a 6m wide road outside a garden in all class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is the electric flux through a cube of side 1 class 10 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The radius and height of a cylinder are in the ratio class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How do you graph the function fx 4x class 9 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Name the states which share their boundary with Indias class 9 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Difference Between Plant Cell and Animal Cell
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is pollution? How many types of pollution? Define it
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.
![arrow-right](/cdn/images/seo-templates/arrow-right.png)